Water Quality Study to Improve Technology and Sustainability of Farmer’s Pond in Banjarpanji Village Sidoarjo - Heryono, Firman; Siswanto, Siswanto; Wijaya, Kemal (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2024)
The technology used in pond processing in Banjar Panji village is still traditional, with minimal labor involvement. This extensive or traditional pond does not utilize windmills, and the feed is natural. The purpose of the study was to study the physicochemical parameters of water quality in fish farming based on the Ministerial Regulation of the Ministry of Marine Affairs and Fisheries No. 75/Permen-KP/2016. The study was conducted in Banjarpanji Village, Tanggulangin District, Sidoarjo Regency, East Java. The study began from January to February 2024. Meanwhile, water sample analysis activities were conducted at the Land Resources Laboratory I and II, Faculty of Agriculture, National Development University "Veteran" East Java. Data collection used a survey method by conducting reviews and direct observations at the research location. The station sample points were determined by purposive sampling based on the distribution of grid divisions. The results showed that most water quality parameters, such as temperature, salinity, pH, dissolved oxygen, ammonia, nitrite, and nitrate, were outside the ideal limits for optimal cultivation. The salinity at all points of the pond was very low, for example, indicating a mismatch with the ideal needs for milkfish cultivation, which requires a specific salinity range for optimal growth. In addition, inadequate dissolved oxygen levels can inhibit the respiration of aquatic organisms and result in dangerous anoxic conditions.